Free sialic acid storage disorder: Progress and promise. (11th June 2021) - Huizing, Marjan; Hackbarth, Mary E.; Adams, David R.; Wasserstein, Melissa; Patterson, Marc C.; Walkley, Steven U.; Gahl, William A.; ,; Adams, David R.; Dobrenis, Kostantin; Foglio, Jessica; Gahl, William A.; et al.
Highlights: FSASD is an underdiagnosed neurodegenerative multisystem lysosomal storage disease. FSASD is caused by defects in the lysosomal free sialic acid exporter SLC17A5. FSASD should be considered in individuals with hypomyelination on brain MRI. The SLC17A5 gene should be included in lysosomal storage disease (LSD) gene panels. A research consortium is generating preclinical data for FSASD drug development. Abstract: Lysosomal free sialic acid storage disorder (FSASD) is an extremely rare, autosomal recessive, neurodegenerative, multisystemic disorder caused by defects in the lysosomal sialic acid membrane exporter SLC17A5 (sialin). SLC17A5 defects cause free sialic acid and some other acidic hexoses to accumulate in lysosomes, resulting in enlarged lysosomes in some cell types and 10-100-fold increased urinary excretion of free sialic acid. Clinical features of FSASD include coarse facial features, organomegaly, and progressive neurodegenerative symptoms with cognitive impairment, cerebellar ataxia and muscular hypotonia. Central hypomyelination with cerebellar atrophy and thinning of the corpus callosum are also prominent disease features. Around 200 FSASD cases are reported worldwide, with the clinical spectrum ranging from a severe infantile onset form, often lethal in early childhood, to a mild, less severe form with subjects living into adulthood, also called Salla disease. The pathobiology of FSASD remains poorly understood and FSASD is likely underdiagnosed. Known patients have experienced a diagnostic delay due to the rarity of the disorder, absence of routine urine sialic acid testing, and non-specific clinical symptoms, including developmental delay, ataxia and infantile hypomyelination. There is no approved therapy for FSASD. We initiated a multidisciplinary collaborative effort involving worldwide academic clinical and scientific FSASD experts, the National Institutes of Health (USA), and the FSASD patient advocacy group (Salla Treatment and Research [S.T.A.R.] Foundation) to overcome the scientific, clinical and financial challenges facing the development of new treatments for FSASD. We aim to collect data that incentivize industry to further develop, obtain approval for, and commercialize FSASD treatments. This review summarizes current aspects of FSASD diagnosis, prevalence, etiology, and disease models, as well as challenges on the path to therapeutic approaches for FSASD.